Evaluation of substrates on the emergence of "araticum-de-terra-fria" (Annona emarginata (Schltdl.) H. Rainer) Seedlings - Baron,Daniel (2011)
Choosing a substrate is the determinant factor for the seedling producer; thus, the aim of this study was to evaluate the effect of different types of substrates on the emergence of "araticum-de-terra-fria" (Annona emarginata (Schltdl.) H. Rainer) seedlings. The experiment was carried out in a greenhouse and the experimental design was in randomized blocks, with three treatments and five replicates of 72 seeds per plot. The treatments consisted of the following substrates: coconut fiber, vermiculite and Plantmax® Citrus. The number of emerged seedlings was weekly counted for 105 days. Data regarding seedling height were obtained, and the emergence velocity index and mean time, besides total emergence percentage and that over time were calculated. Results from total mean emergence percentage, seedling height, emergence velocity index (EVI), and mean emergence time (MET) were subjected to analysis of variance and means were compared by the Tukey's test at 5% significance. The curves concerning the emergence percentage over time were fit by the logistic growth equation for each treatment and the means of each parameter (A, B, C) were compared by the Duncan's test at 5% significance. The substrates vermiculite led to the highest values of emergence percentage differing from the PlantMax® Citrus, but not of the coconut fiber, however the vermiculite promoted seedling height in a shorter time; therefore, this substrate is recommended for the initial development of "araticum-de-terra-fria" (Annona emarginata (Schltdl.) H. Rainer) seedlings.